Dynamic response enhancement of BDFIG using vector control scheme based internal model c ontrol - Ahsanullah Memon; Mohd Wazir Mustafa; Shadi Khan Baloch; Attaullah Khidrani; Touqeer Ahmed (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
Doublefed induction generator(DFIG) has shown tremendous success inwind turbines due to its flexibility and ability to regulate the active andreactive power. However, the presence of brushes and slip rings affects itsreliability, stability, and power quality. Furthermore, itdoes not providepromising outcomes in case of faults even in presence of the crowbar circuit.In contrast, thebrushless doubly fed induction generator(BDFIG) is a morereliable option for wind turbines than its mentioned counterpart due to theabsence of the brushes and slip rings. This research work as such attempts toimprove the dynamic performance of thevector control(VC)oriented powerwinding (PW) stator flux-based BDFIG by optimally selecting theproportional-integral(PI) gains throughinternalmodel control(IMC)approach. The proposed control scheme is utilized to regulate the speed,torque, and reactive power of the considered BDFIG independently. Contraryto the previous literature where the “trial and error method” is generallyutilized, the current research work uses the IMC for selecting the mostsuitable PI parameters, thus reduces the complexity, time consumption, anduncertainty in optimal selection. The considered BDFIG based wind turbinewith the proposed control scheme provides a better BDFIG control designwith an enhanced dynamic response as compared to that of the same withDFIG under identical operating conditions and system configurations.